A Case of Congenital Malignant Spinal Cord Glioma as a Cause of Congenital Ascites in a Neonate - Bianca Karber; Lenore Omesi; Sunny Chang; Andrew Handel; Monica Hegedus; Echezona Maduekwe (Case Reports in Pediatrics)
Congenital ascites is rare, but when it occurs, urinary ascites secondary to posterior urethral valve obstruction is the most common, and tumors are the least. Among the tumors in the pediatric population, the central nervous system tumors are common, but spinal cord tumors are rare. We describe a very rare case of congenital malignant spinal cord glioma presenting as isolated congenital ascites secondary to neurogenic bladder. A female infant was diagnosed sonographically with isolated congenital ascites at 40 weeks’ gestational age, with uneventful development prior to 40 weeks’ gestational age. Magnetic resonance imaging of the spine done within the first week of life identified a lobulated spinal mass with heterogeneous enhancement within the conus medullaris. Spinal fluid analysis showed evidence of small round blue cells and the pathology from the excision biopsy of the mass confirmed a WHO grade III or IV malignant glioma. The postoperative course was uneventful with resolution of the ascites and spontaneous micturition. The patient was discharged home without an indwelling urinary catheter. We report the first documented case of a newborn infant with isolated congenital ascites from neurogenic bladder secondary to a spinal cord glioma.